Mycobacteria as a cause of infective exacerbation in bronchiectasis. Issue 805 (November 1992) - Chan, C. H.; Ho, A. K.; Chan, R. C.; Cheung, H.; Cheng, A. F.
Abstract : In 91 patients with bronchiectasis seen over 6 years, a positive mycobacterial culture was obtained in 12 cases (13%). The organisms isolated were Mycobacterium tuberculosis in nine cases, Mycobacterium avium in two cases and Mycobacterium tuberculosis and chelonei were obtained on separate occasions in one case. Computed tomography and/or bronchography showed that the bronchiectatic changes commonly involved the lower lobes and to a lesser extent, the middle and lingula lobes. In none of these 12 cases was tuberculosis strongly suspected on clinical or radiological grounds. We conclude that mycobacterial infections are common in patients with bronchiectasis and sputum should be cultured for mycobacteria periodically in these patients. In doubtful cases, bronchoscopy may be helpful to obtain a positive mycobacterial culture.